2019
DOI: 10.1007/s11469-019-00167-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Italian Versions of the Gambling Urge Scale (GUS) and the Gambling Refusal Self-Efficacy Questionnaire (GRSEQ)

Abstract: Gambling urges and gambling refusal self-efficacy beliefs play a major role in the development and maintenance of problem gambling. This study aimed to translate the Gambling Urge Scale (GUS) and the Gambling Refusal Self-Efficacy Questionnaire (GRSEQ) from English to Italian (GUS-I, GRSEQ-I) and to test their factor structure, internal consistency, construct validity, concurrent validity, and gender differences in 513 individuals from the Italian community. Factor structure and construct validity were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Addiction science has predominantly conceptualized self-efficacy in terms of perceived confidence to resist engaging in addictive behaviors in high-risk situations, but self-efficacy measures frame such resistance slightly differently, including confidence in controlling addictive behavior [45], resisting the urge to engage in addictive behavior [46], avoiding addictive behavior [47], refusing to engage in addictive behavior [48], or abstaining from addictive behavior [49]. Regardless of how resistance is framed, cross-sectional studies have consistently found that self-efficacy is negatively associated with both gambling behavior and problem gambling severity [22,23,45,47,[49][50][51][52][53] and accurately discriminates between nonproblem and problem gambling samples [48,52]. Qualitative research supports these findings, suggesting that self-efficacy is a key construct in preventing relapse, which in turn increases motivation and commitment to maintain abstinence over time; however, the protective effect of self-efficacy weakens once relapse has occurred [27,28].…”
Section: Gambling Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Addiction science has predominantly conceptualized self-efficacy in terms of perceived confidence to resist engaging in addictive behaviors in high-risk situations, but self-efficacy measures frame such resistance slightly differently, including confidence in controlling addictive behavior [45], resisting the urge to engage in addictive behavior [46], avoiding addictive behavior [47], refusing to engage in addictive behavior [48], or abstaining from addictive behavior [49]. Regardless of how resistance is framed, cross-sectional studies have consistently found that self-efficacy is negatively associated with both gambling behavior and problem gambling severity [22,23,45,47,[49][50][51][52][53] and accurately discriminates between nonproblem and problem gambling samples [48,52]. Qualitative research supports these findings, suggesting that self-efficacy is a key construct in preventing relapse, which in turn increases motivation and commitment to maintain abstinence over time; however, the protective effect of self-efficacy weakens once relapse has occurred [27,28].…”
Section: Gambling Self-efficacymentioning
confidence: 99%
“…Despite this conceptual confusion, the emerging cross-sectional literature highlights the important role that craving plays in the maintenance, exacerbation, and relapse of gambling problems. Specifically, findings suggest that gambling cravings are positively associated with problem gambling severity [ 22 , 23 ] and gambling relapse [ 24 ], negatively associated with abstinence [ 24 , 25 ], and are among the most frequent precipitants of relapse [ 26 ]. These findings are supported by qualitative research in which gambling cravings have been identified as a key construct associated with an increased risk of gambling relapse [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%